THE IMPORTANCE OF PUBLIC POLICIES AND ASSISTANCE TO VICTIMS OF HUMAN TRAFFICKING: A LITERATURE REVIEW - Alves-Lazaro, Anna (Revista Gênero e Interdisciplinaridade, 2025)
Introduction: Human trafficking is increasingly victimizing more people, and the consequences of these actions are drastic, affecting various aspects of victims’ lives and impacting their overall integrity. Public policies can play a fundamental role in both preventing and assisting victims, promoting comprehensive and effective support.Objective: To synthesize, based on the literature, the importance of public policies and assistance for individuals who are victims of human trafficking.Methodology: This study is a bibliographic review that followed the steps of formulating the guiding question. Subsequently, literature searches or sampling, data collection, critical analysis of the selected studies, and discussion of the results were conducted. The databases used were LILACS, Google Scholar, and SciELO. The search for descriptors was carried out in both English and Portuguese, with the main ones being public policies, human trafficking, and Brazil.Results: This bibliographic review identifies that public policies play a crucial role in combating human trafficking and supporting victims, being essential tools for prevention, protection, and social reintegration. Additionally, comprehensive victim assistance, including psychological, legal, and socioeconomic support, is indispensable for their recovery and reintegration into society. However, the studies point out significant gaps in the development and implementation of more robust and effective actions. There is a pressing need to develop more public policies and assistance strategies in this context, as well as to promote debates, events, and scientific studies on the subject. This is necessary because society as a whole is still far from achieving an effective assistance framework for human trafficking victims.Conclusion: It can be concluded that more public policies to combat human trafficking are necessary. However, the results highlight significant gaps in the development and implementation of more robust and effective measures.